Carbon nanotubes catalytic activity in the ethylene hydrogenation. Issue 12 (2nd December 2018) - Bychko, Igor; Strizhak, Peter
Abstract: This work shows, for the first time, that the multi-walled carbon nanotubes (MWCNTs) exhibit the catalytic activity in the ethylene hydrogenation. MWCNTs with the average diameter of 35 nm were prepared by CVD from ethylene as a carbon source at 700 °C. TEM, SEM, and XRD indicate that MWCNTs are characterized by a sufficiently high defectiveness. FTIR highlights that the catalytic process occurs in the presence of the hydroxyl and carbonyl surface groups. We demonstrate the high catalytic stability of MWCNTs at temperatures up to 400 °C.